2008
DOI: 10.1007/s11259-008-9078-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative susceptibility of chickens, turkeys and ducks to infectious bursal disease virus using immunohistochemistry

Abstract: Twenty chicks, 12 turkey poults and 10 ducklings, all 5 weeks old were infected with 2 x 10(3.5) chick LD(50) IBD virus to determine the course of the virus in the 3 poultry species. Uninfected control birds were kept separately. Two infected and 2 control birds/species were euthanized at time intervals between 3 and 168 hours post infection (pi). Sections of thymus, bursa of Fabricius, spleen, liver, kidney, proventriculus and ceacal tonsil were stained for the detection of IBD virus antigen using immunoperox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…In various previous experimental studies, IBDV antigens have been detected in macrophages within follicles, the interstitium, and the lymphoid cells of bursa of Fabricius, e.g., by Oladele et al . [ 21 ], but in the present study, the viral antigens were found mainly associated with bursal lymphoid cells and in bursal epithelium in some cases ( Figure-4 ). The findings can be related to the findings of Tippenhauer et al .…”
Section: Resultscontrasting
confidence: 51%
See 3 more Smart Citations
“…In various previous experimental studies, IBDV antigens have been detected in macrophages within follicles, the interstitium, and the lymphoid cells of bursa of Fabricius, e.g., by Oladele et al . [ 21 ], but in the present study, the viral antigens were found mainly associated with bursal lymphoid cells and in bursal epithelium in some cases ( Figure-4 ). The findings can be related to the findings of Tippenhauer et al .…”
Section: Resultscontrasting
confidence: 51%
“…The presence of viral antigen was also appreciated in the bursal interfollicular connective tissue ( Figure-5 ) as well as the bursal epithelium which was also reported by Oladele et al . [ 21 ]. The distribution of viral antigen varied from being localized ( Figure-6 ) to focal to diffuse.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two serotypes of IBDV (1 and 2) were distinguished by cross-virus neutralization [4]. The IBDV strains of serotype 1 are pathogenic to chickens [5] and further classified as classical virulent IBDV (cvIBDV), very virulent IBDV (vvIBDV), antigenic variant IBDV (avIBDV), and attenuated IBDV (atIBDV) [6]. Strains of serotype 2 are naturally avirulent for chickens [7, 8].…”
Section: Introductionmentioning
confidence: 99%